THE BIOMECHANICAL CHARACTERISTICS OF INTRAORAL BONE RECONSTRUCTION MATERIALS - Doriana Agop Forna; Claudiu Topoliceanu; Ovidiu Stamatin; Norin Forna; Corneliu Munteanu; Marcelin Benchea; Alexandra Davidescu; Bianca Toader; Biciusca Raluca; Norina Forna (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study The aim of this literature review is to provide a comprehensive comparative analysis of the characteristics of oral bone reconstruction materials, specifically bovine, equine, porcine, and tricalcium phosphate. The study aims to explore the biomechanical properties, biocompatibility, and clinical implications of these materials, enabling a better understanding of their potential applications in oral bone reconstruction procedures. Materials and Methods A systematic literature search was conducted using electronic databases, including PubMed and Scopus, to identify relevant studies published up to the present. Keywords such as "oral bone reconstruction materials," "bovine," "equine," "porcine," and "tricalcium phosphate" were used to identify articles that focused on the characteristics and comparison of these materials. Studies reporting on biomechanical properties, biocompatibility evaluations, and clinical outcomes were included in the review. Results The literature review revealed variations in the characteristics of oral bone reconstruction materials. Bovine bone reconstruction material demonstrated superior mechanical properties, including higher compressive and tensile strength, as well as a higher elastic modulus. Porcine bone reconstruction material exhibited intermediate properties, balancing mechanical strength and biocompatibility. Equine bone reconstruction material demonstrated relatively lower mechanical properties but may offer advantages in specific biological contexts. Tricalcium phosphate, a synthetic material, displayed controlled resorption potential but lower mechanical strength. Discussions The observed variations in the characteristics of oral bone reconstruction materials have implications for their clinical applications. Conclusions The comparative analysis of oral bone reconstruction materials highlights the importance of selecting materials based on individual patient needs, clinical requirements, and treatment goals. Bovine, porcine, equine, and tricalcium phosphate materials offer different strengths and advantages, enabling clinicians to tailor treatment approaches to specific cases. Further research, including long-term clinical studies and advancements in material development, is needed to enhance our understanding and use of these materials in oral bone reconstruction procedures, ultimately improving patient outcomes.